TRADISI MARSIPULUT SEBAGAI SIMBOL BUDAYA DALAM PROSESI MARPOKAT PADA TAHAPAN PRA-PERKAWINAN DI DESA RAO-RAO LOMBANG, MANDAILING NATAL - Rahmad Hidayat Lubis; Akhrif Yahsya; Ummi Kalsum; Nur Mawaddah; Ahmad Rosyadi; Sumita Ulfah; Nur Aminah; Rigon Hasibuan; Tri Pratiwi; Riski Padilah; Winda Amalia (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The marsipulut tradition in Rao-rao Lombang Village, Mandailing Natal, represents a manifestation of local wisdom that plays an important role in the marpokat or pre-marital deliberation process. This study examines the role of marsipulut as a cultural symbol as well as the socio-cultural values embedded within it. Marsipulut, a dish made of glutinous rice mixed with grated coconut and palm sugar, is not only regarded as a traditional delicacy but also as a representation of togetherness, respect, and commitment among families involved in the marriage agreement process. A qualitative research method with an ethnographic approach was employed, involving participatory observation, in-depth interviews with traditional leaders and community figures, and the analysis of local documents. The findings reveal that marsipulut functions as a medium of symbolic communication that reinforces social structure, fosters solidarity, and codifies norms related to etiquette and responsibility in the pre-marital stages. Furthermore, the marsipulut serving ceremony affirms the boundaries of local cultural identity amid socio-cultural changes. The study recommends preserving the marsipulut practice through cultural education and documentation to ensure the continuity of cultural values that sustain social cohesion in Rao-Rao Lombang. This research contributes to the development of local anthropological studies and cultural policy by providing empirical evidence of the relationship between the materiality of ritual food and the structure of values. Further studies are suggested to explore intergenerational dynamics and the impact of modernization on marsipulut practices for more adaptive preservation strategies.